Development of Microsoft Powerpoint Learning Media on Chemical Bonding Material - Hamas Abthal (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
This Research has been conducted to development of Microsoft Powerpoint media on chemical bonding material. Based on observations and interviews with high school IT students Alfityan Aceh Besar shows the use of instructional media on chemical bonding material is still not applied in learning students that cause difficulty understanding about abstract material. The purpose of this study was to determine the feasibility of learning media developed and determine students' responses to the development of Microsoft Powerpoint media on chemical bonding material. The design of this study is the design of Research and Development (R&D). The subjects of this study were 13 high school IT students Alfityan Aceh Besar. Data collection techniques using validation and questionnaires. Validation and response data were analyzed using quantitative descriptive techniques. The percentage of validation results obtained by the media expert validator was 77.9% and the percentage of material expert validators was 92.2%. So the Microsoft Powerpoint learning media is categorized as suitable for use in chemical bonding material. The results of student responses to the Microsoft Powerpoint learning media that is 94.9% of students responded with very good criteria for the development of Microsoft Powerpoint media on chemical bonding material.